Halal Lifestyle as A New Lifestyle in Modern Era: Demand Function Theory of Marshall and Ibn Taimiyah - Masruroh, Nikmatul; Raziqi, Ahmad; Hariyanto, Al Furqon Dono (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2021)
The Muslim community has grown to be the world’s largest population. Muslims have become a priority for business people and manufacturers who understand Muslim life patterns. Nowadays, manufacturers do not hesitate to use the halal label to reap huge revenues from Muslims. According to the GIE-report for 2019 to 2020, Muslim expenditure on the purchase of goods and services in six industries of food, finance, medicine, cosmetics, fashion, and travel and tourism has reached 2.2 trillion with 5.2% YoY growth from 1.8 billion Muslims worldwide. This draws a rosy picture of the development of the halal industry that Muslims have turned into a potential market. Products adhering to Islamic law are what manufacturers must consider having their goods sold well. The sharia trend has become a new lifestyle, particularly for millennials. The rise of Islamophobia is one of the reasons for the ascending trend of sharia-compliant lifestyles in the modern age. This paper highlights the sharia modes of consumption practiced by Muslims by employing literature review as a research methodology. Referring to the Marshallian demand function, the higher the demand, the higher the satisfaction, yet, even if it is labeled halal, the additional satisfaction decreases. This is in stark contrast to Ibn Taymiyah asserting that market demand depends on shifting preferences. Muslims are increasingly focused on the halal lifestyle due to ever-changing tastes based on economic reasoning.